Fibrosis pulmonar más infección respiratoria aguda baja en paciente femenino de 73 años de edad. - Villacis Campuzano, Génesis Yamileth (2020)
Pulmonary fibrosis is characterized by an abnormal healing process, with excess fibrous tissues, chronic, progressive pathology limited to the lungs of unknown etiology, which is why it is called idiopathic that affects adults over 50 years of age with a progressive deterioration of lung function. A case study has been carried out, with a diagnosis of pulmonary fibrosis and treatment of this pathology in a 73-year-old female patient, presenting with fever over 38 ° C, cough, respiratory distress, sore throat, plus unquantified thermal rise and a little lethargic, initial treatment is prescribed, he presents a severe bronchospasm crisis, for which he proceeds to control with nebulization plus salbutamol. Complementary examinations revealed pulmonary condensation with pneumonia involving the left lower lobe. The analysis of the examinations reached the diagnosis of pulmonary fibrosis plus acute lower respiratory infection. The study is important given the need to provide information to patients who have already been diagnosed with pulmonary fibrosis to understand and cope with the disease, the risk factors in acute lower respiratory infection in patients with pulmonary fibrosis were identified, in addition to the clinical manifestations and proper management of the respiratory therapist, facilitated the treatment preventing complications, it is concluded that the evolution and follow-up of the patient was favorable, it is recommended that these patients should be in environments under their health condition, avoiding the evolution of new infections.